ANALISIS EFISIENSI PENERAPAN PERATURAN PEMERINTAH NOMOR 46 TAHUN 2013 TERHADAP PERTUMBUHAN JUMLAH WAJIB PAJAK DAN KONTRIBUSINYA PADA PENERIMAAN PAJAK KPP PRATAMA BINJAI - Junawan (Jurnal Akuntansi Bisnis dan Publik, 2019)
The objective of the research was to determine whether the implementation of Government Regulation No. 46 of 2013 (PP 46 of 2013) improves the efficiency of fulfilling tax obligations for taxpayers, and provides an increase in the growth of the number of taxpayers so that it will provide an increase in tax revenue contribution to Binjai Tax Office (KPP Pratama Binjai). The sampling technique used in this study uses the census method with the criteria of using the total number of individual and corporate taxpayers with omzet less than or equal to 4.8 billion a year registered at the KPP Binjai Pratama Tax Service Office totaling 1,256 taxpayers. The analytical method uses quantitative descriptive analysis with a Comparative approach, and the hypothesis test used is the Paired Sample T-test. The result of the research show that the application of PP 46 of 2013 provides an increase in the efficiency of fulfilling tax obligations for taxpayers than before the enactment of this government regulation, and increases the growth of the number of taxpayers, so that the contribution of tax revenue increases in Binjai Primary Tax Office compared to before the implementation of PP 46 of 2013.